John Steinbeck in USSR. - unknown:::Creator::::::::::::
John Steinbeck with Irakli Abashidze playing wooden flutes. Abashidze, was a Georgian poet, literary scholar and the First Secretary of the Georgian Writer's Union, called it an 'American-Georgian group of musicians.' Photograph taken during the Steinbeck's visit in Oct. 27-31, 1963. Original in safe